Porphyromonas gingivalis regulates atherosclerosis through an immune pathway - Ruan, Qijun; Guan, Peng; Qi, Weijuan; Li, Jiatong; Xi, Mengying; Xiao, Limin; Zhong, Sulan; Ma, Dandan; Ni, Jia (Frontiers in Immunology, 2023)
Atherosclerosis (AS) is a chronic inflammatory disease, involving a pathological process of endothelial dysfunction, lipid deposition, plaque rupture, and arterial occlusion, and is one of the leading causes of death in the world population. The progression of AS is closely associated with several inflammatory diseases, among which periodontitis has been shown to increase the risk of AS. Porphyromonas gingivalis (P. gingivalis), presenting in large numbers in subgingival plaque biofilms, is the "dominant bacterium" in periodontitis, and its multiple virulence factors are important in stimulating host immunity. Therefore, it is significant to elucidate the potential mechanism and association between P. gingivalis and AS to prevent and treat AS. By summarizing the existing studies, we found that P. gingivalis promotes the progression of AS through multiple immune pathways. P. gingivalis can escape host immune clearance and, in various forms, circulate with blood and lymph and colonize arterial vessel walls, directly inducing local inflammation in blood vessels. It also induces the production of systemic inflammatory mediators and autoimmune antibodies, disrupts the serum lipid profile, and thus promotes the progression of AS. In this paper, we summarize the recent evidence (including clinical studies and animal studies) on the correlation between P. gingivalis and AS, and describe the specific immune mechanisms by which P. gingivalis promotes AS progression from four aspects (immune escape, blood circulation, lymphatic circulation, and induction of autoantibodies), providing new insights into the prevention and treatment of AS by suppressing periodontal pathogenic bacteria.